CONTEMPORARY THEORIES OF ADULT LEARNING - Babajeva, Ludmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Due to the adult learning theory transition from cognitive to comprehensive aspects, this article analyses contemporary theoretical notions about adult’s learning. In order to characterise the modern view on adult, the most recent insights into the education of whole adult person (P. Jarvis), three dimensions of learning (K.Illeris) and the critical theory contribution (S.D. Brookfield) will be discussed. All of mentioned, globally-renowned theorists are of the same opinion and contribute to the general adult learning theory – P. Jarvis pictures the learning process from a viewpoint of a human as holistic organism, K.Illeris develops his theory in relation to the pedagogical conditions of learning, whereas Brookfield discusses an adult in the context of social, political and democratic concept.